PENGARUH LATIHAN PUSH UP TERHADAP DAYA TAHAN OTOT LENGAN PADA SISWA PROGRAM KEAHLIAN TATA BOGA SMK NEGERI 1 ABUNG SELATAN - Putri Dea Pelangi; Adinda Siti Arafah; Putri Destawati; Darwanto (KAMPUS AKADEMIK PUBLISING, 2026)
Arm muscular endurance is one of the physical fitness components that plays an important role in supporting the practical activities of Culinary Arts students, particularly in tasks that involve lifting kitchen equipment, stirring dough, and standing for extended periods in the production area. This study aims to examine the influence of push-up training on arm muscular endurance among Culinary Arts students at SMK Negeri 1 Abung Selatan, while also exploring its relationship with general physical endurance capacity as represented by a running test. The study employed a quantitative descriptive-correlational approach involving 30 students (15 male and 15 female) who were assessed through a one-minute push-up test and a three-minute running test. Data were analyzed descriptively and tested for association using Pearson's correlation coefficient. The results show that the average push-up capacity was 21.6 repetitions per minute, with male students (mean 25.7) consistently achieving a higher number of repetitions than female students (mean 17.5). A moderate positive correlation was also found between push-up capacity and running distance (r = 0.55), indicating that arm muscular endurance contributes to broader physical work capacity. Drawing on the principles of overload, physiological adaptation, and specificity of training, these findings reinforce the argument that structured and sustained push-up training has the potential to improve arm muscular endurance among vocational high school students, thereby supporting their physical readiness for Culinary Arts practice. This study recommends integrating arm-strengthening exercises into physical education and extracurricular programs at SMK Negeri 1 Abung Selatan.